FEATURES OF THE MIXED SENSITIVITY H-OPTIMIZATION FOR THE TWO-DEGREE-OF-FREEDOM CONTROLLER - Sushchenko, Olga; Chaplay, Irina (Proceedings of National Aviation University (archive), 2012)
The paper is devoted to the actual issue of the robust two-degree-of-freedom controller design. The statement of the problem for the robust optimization of the two-degree-of-freedom controller by the method of mixed sensitivity is represented. The expression for the cost function of the mixed sensitivity method for the system with the two-degree-of-freedom controller, taking into consideration the influence of disturbances, is obtained. The components of the generalized system with the two-degree-of-freedom controller and principles of the weighting transfer functions introduction are defined. The transformation of the formulated problem to the - optimization which may be implemented by the MATLAB software is carried out.